2013
DOI: 10.1073/pnas.1306942110
|View full text |Cite
|
Sign up to set email alerts
|

HIF isoforms in the skin differentially regulate systemic arterial pressure

Abstract: Vascular flow through tissues is regulated via a number of homeostatic mechanisms. Localized control of tissue blood flow, or autoregulation, is a key factor in regulating tissue perfusion and oxygenation. We show here that the net balance between two hypoxia-inducible factor (HIF) transcription factor isoforms, HIF-1α and HIF-2α, is an essential mechanism regulating both local and systemic blood flow in the skin of mice. We also show that balance of HIF isoforms in keratinocyte-specific mutant mice affects th… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
58
0
1

Year Published

2014
2014
2023
2023

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 59 publications
(64 citation statements)
references
References 41 publications
2
58
0
1
Order By: Relevance
“…These results demonstrate that mitochondria act as oxygen sensors in vivo, promoting HIF activation and adaptation to hypoxic conditions. While it is unclear why deletion of VHL in the epidermis resulted in early mortality, it was recently shown that in addition to regulating hypoxic adaptation, epidermal HIF levels regulate systemic arterial pressure and thermoregulation in mice (Cowburn et al, 2013). Thus, our results add to the increasing evidence for the importance of oxygen sensing and HIF activation within the epidermis for organismal homeostasis.…”
Section: Discussionmentioning
confidence: 99%
“…These results demonstrate that mitochondria act as oxygen sensors in vivo, promoting HIF activation and adaptation to hypoxic conditions. While it is unclear why deletion of VHL in the epidermis resulted in early mortality, it was recently shown that in addition to regulating hypoxic adaptation, epidermal HIF levels regulate systemic arterial pressure and thermoregulation in mice (Cowburn et al, 2013). Thus, our results add to the increasing evidence for the importance of oxygen sensing and HIF activation within the epidermis for organismal homeostasis.…”
Section: Discussionmentioning
confidence: 99%
“…For example, HIF-1a promotes cell cycle arrest, whereas HIF-2a promotes progression through the cell cycle, likely in a cell context-dependent manner (Keith et al 2012). In murine macrophages, keratinocytes, and endothelial cells, Hif-1a promotes NO production through activation of the inducible NO synthase (Nos2) gene, whereas Hif-2a inhibits NO production through the induction of the arginase (Arg) gene Branco-Price et al 2012;Cowburn et al 2013). Finally, Hif1a +/À mice display blunted respiratory responses to chronic hypoxia, while Hif2a +/À mice display exaggerated carotid body sensitivity to hypoxia ( Fig.…”
Section: The Hif Pathwaymentioning
confidence: 99%
“…Johnson and colleagues have demonstrated that the two hypoxia-inducible factor (HIF) transcription factors HIF-1α and HIF-2α critically control the NO equilibrium in the skin, with keratinocyte-HIF-2α promoting vascoconstriction, while keratinocyte-HIF-1α mediates vasodilation [5]. Mice with keratinocyte-specific deletion of HIF-1α therefore had higher blood pressure, while HIF-2α deletion resulted in low blood pressure levels and body temperature loss.…”
Section: Blood Pressure Regulation: Only Skin Deep and Related To Skmentioning
confidence: 99%